Victimization status among persons with disabilities and its predictors: Evidence from Bangladesh National Survey on Persons with Disabilities - Mizanur Rahman; Md Shohel Rana; Gulam Khandaker; Md Mostafizur Rahman; Md. Nuruzzaman Khan (PLoS ONE, 2025)
Background Persons with disabilities often face various forms of victimization, yet there is limited research exploring this phenomenon in Bangladesh. This study aims to investigate the victimization status among persons with disabilities and identify its predictors. Methods Data of 4293 persons with disabilities analyzed in this study were extracted from the 2021 National Survey on Persons with Disabilities. Victimization status (yes, no) was considered as the outcome variables. Explanatory variables considered were factors at the individual, household, and community levels. A multilevel mixed-effect logistic regression model was used to explore the association of the outcome variable with explanatory variables by dividing the total sample into age groups of 0–17 years, 18–59 years, and ≥ 60 years. Results The study found that 44% of persons with disabilities in Bangladesh experienced victimization, primarily involving neighbours (90.64%), relatives (43.41%), friends (28.41%), and family members (27.07%). Among persons aged 0–17 years, increasing age was associated with a higher likelihood of being victimized, while residing in the wealthiest households or in certain divisions like Khulna and Rangpur was associated with lower likelihoods. Conversely, among respondents aged 18–59 and ≥ 60 years, increasing age was associated with a lower likelihood of being victimized. Unmarried respondents aged 18–59 years had an increased likelihood of victimization compared to married individuals. For persons with disabilities aged ≥ 60 years, a higher level of schooling was associated with a reduced likelihood of being victimized. We also found divisional differences in the likelihood of victimization, with respondents residing in Chattogram, Khulna, Mymensingh, Rangpur, and Sylhet reporting lower likelihoods compared to those residing in the Barishal division, among persons with disabilities aged 18–59 and ≥ 60 years. Conclusion This study’s findings underscore that around 4 in 10 persons with disabilities are being victimized. Tailored programs and awareness-building initiatives covering neighbours, relatives, friends, and family members of persons with disabilities are important to ensure dignified lives for this population.